Reforming the Tax System in Japan to Promote Fiscal Sustainability and Economic Growth - Jones, Randall S.. (OECD Publishing, 2008)
Tax reform is an urgent priority, as Japan needs as much as 5% to 6% of GDP of additional government revenue just to stabilise public debt, which has risen to 180% of GDP. In addition to raising revenue, tax reform should promote economic growth, address the deterioration in income distribution and improve the local tax system. Additional revenue should be obtained primarily by increasing the consumption tax rate, currently the lowest in the OECD area, while broadening the personal and corporate income tax bases. The corporate tax rate, now the highest in the OECD area, should be cut to promote growth, while eliminating aspects of the tax system which discourage labour supply and distort the allocation of capital. Japan should also consider introducing an Earned Income Tax Credit to promote equity. The local tax system should be simplified, increasing reliance on existing taxes on property, income and consumption
Keywords: Economics; Japan